(untitled) (Международный научный журнал «Инженер», 2026)
The article presents the results of research on optimising the composition of complex modified selfcompacting fine-grained concrete mixtures intended for vibration-free and low-vibration construction technologies. The aim of the work was to establish rational component ratios that ensure an optimal balance between the rheological and strength characteristics of concrete. The parameters considered for optimisation were compressive strength at 1, 7 and 28 days, flexural strength, average density, and watercement ratio. It was found that the use of a complex modifier, including mineral and chemical additives, contributes to a reduction in the water-cement ratio while maintaining the necessary mobility, increases early and final strength, and ensures the formation of a dense and homogeneous material structure without the use of vibration compaction. The results obtained can be used in the development of energy-efficient technologies for monolithic construction using self-compacting fine-grained concretes.